Monooxime reactivators of acetylcholinesterase with (E)-but-2-ene linker: preparation and reactivation of tabun- and paraoxon-inhibited acetylcholinesterase - Musilek, Kamil; Holas, Ondrej; Jun, Daniel; Dohnal, Vlastimil; Gunn-Moore, Frank; Opletalova, Veronika; Dolezal, Martin; Kuca, Kamil (Bioorganic & medicinal chemistry, 2007)
Acetylcholinesterase reactivators are crucial antidotes for the treatment of organophosphate intoxication. Fifteen new monooxime reactivators of acetylcholinesterase with a (E)-but-2-ene linker were developed in an effort to extend the properties of K-oxime (E)-1-(4-carbamoylpyridinium)-4-(4-hydroxyiminomethylpyridinium)-but-2-ene dibromide (K203). The known reactivators (pralidoxime, HI-6, obidoxime, K075, K203) and the new compounds were tested in vitro on a model of tabun- and paraoxon-inhibited AChE. Monooxime reactivators were not able to exceed the best known compounds for tabun poisoning, but some of them did show reactivation comparable with known compounds for paraoxon poisoning. However, extensive differences were found by a SAR study for various substitutions on the non-oxime part of the reactivator molecule.
Keywords: vztahy mezi strukturou a aktivitou; acetylcholinesterasa; cholinesterasové inhibitory; antidota; Acetylcholinesterase; Drug Design; Animals; Cholinesterase Reactivators; Paraoxon; organofosfáty; reaktivátory cholinesterasy; paraoxon; krysa rodu Rattus; oximy; Rats; Cholinesterase Inhibitors; zvířata; Organophosphates; Oximes; Structure-Activity Relationship; Antidotes; racionální návrh léčiv